2008
DOI: 10.1295/polymj.pj2007217
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Mechanical Behavior of Scarcely Crosslinked Poly(dimethyl siloxane) Gel: Effect of Strand Length Polydispersity

Abstract: Nonlinear mechanical behavior was examined for a scarcely crosslinked poly(dimethyl siloxane) gel (referred to as Gel-1/1) under constant-rate elongation and large step shear strains. The average molecular weight of the gel strands evaluated from the equilibrium modulus in the linear viscoelastic regime was M c ¼ 190 Â 10 3 , and the strands had a significantly broad molecular weight distribution, M w =M n ¼ $ 600 as estimated by fitting the linear viscoelastic moduli with a Rouse network model. In the elongat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…They have summarized that the examined arm length contrast does not significantly affect the toughness of resultant gels. We note that if further contrast is introduced, the inhomogeneous stretching of strands probably depresses the toughness, as suggested by earlier studies for end-linked 17,18 and randomly cross-linked 19 poly (dimethylsiloxane) (PDMS) elastomers.…”
Section: Introductionsupporting
confidence: 68%
“…They have summarized that the examined arm length contrast does not significantly affect the toughness of resultant gels. We note that if further contrast is introduced, the inhomogeneous stretching of strands probably depresses the toughness, as suggested by earlier studies for end-linked 17,18 and randomly cross-linked 19 poly (dimethylsiloxane) (PDMS) elastomers.…”
Section: Introductionsupporting
confidence: 68%
“…The rheological properties of sparse polydimethylsiloxane (PDMS) networks were intensively investigated by Takahashi et al . , These PDMS gels were composed of an infinite sparse network with considerable amounts of soluble components (finite clusters) owing to the low degree of reaction extent. They showed that the sparse network structures enhanced the ultimate extensibility and decreased the gel modulus because of the long average chain length of network strands and low network backbone concentration. , However, the nonlinear elasticity characteristics of sparse networks still need to be characterized. As an extremely sparse network, one can consider a near-critical gel slightly beyond the gelation threshold.…”
Section: Introductionmentioning
confidence: 99%
“…The present study investigates the nonlinear elasticity of extremely sparse networks in near-critical gels employing biaxial stretching. Nonlinear stress–strain behaviors of various types of sparse networks have been reported. , However, they are limited to uniaxial stretching or compression. While uniaxial deformation is a special type among all accessible deformations of gels, unequal biaxial stretching with varying independently the strains in two orthogonal directions covers a wide range of deformations. ,, The biaxial stress–strain data provide a definite basis for a comprehensive understanding of the nonlinear elasticity of elastomers and gels, e.g., the unambiguous determination of strain energy density function. , Because near-critical gels are composed of an extremely sparse infinite network and a large number of finite clusters, the modulus is so low (typically of the order of 10 3 Pa) that they can undergo considerable bending deformation by their own weight, resulting in an obstacle for mechanical testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, organic crosslinkers can gel slowly and bear relatively high temperatures, prompting them to be candidates for chemical flooding in enhanced oil recovery. The different types of crosslinkers lead to discrepancies in rheological properties, salt resistance and temperature resistance; moreover, crosslinking density and junction size also have an effect on these properties, [13][14][15] hence comprehension of the structure-function relation has become increasingly important. However, it is difficult to characterize the structure and composition of the crosslinked products with poor solubility and meltability, hence the crosslinked structure and mechanism are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%